Dietary supplementation of mannan oligosaccharide improves the immune responses and survival of marron, Cherax tenuimanus (Smith, 1912) when challenged with different stressors - Sang, Huynh; Ky, Le; Fotedar, Ravi (Elsevier, 2009)
Three trials were conducted to determine the effects of mannan oligosaccharide (Bio-Mos) on the immune responses of marron. In the first trial marron were challenged with Vibrio mimicus infection, in the second with NH3 exposure and in the third, the marron were exposed to air during a simulated live transportation trial. For V. mimicus infection and live transportation trials, marron (10.44 0.20 g and 4.44 0.20 g initial weights, respectively) were fed three different diets containing 0% (control diet), 0.2% and 0.4% Bio-Mos for 30 days and 112 days respectively before challenge, whereas for the NH3 exposure trial, marron (94 2.17 g initial weight) were reared with the control diet and 0.4% Bio-Mos diet for 42 days before exposure to NH3. Marron were examined for survival and total haemocyte count (THC), differential haemocyte count (DHC), haemolymph clotting time, bacteraemia and lysosomal membrane stability as indicators of immune responses during the course of the challenge. Survival of marron infected with bacteria and exposed to NH3, were significantly improved when fed Bio-Mos. THCs were significantly reduced in marron fed the control diet when they were infected with bacteria and subjected to live transportation while it remained unchanged in the marron fed the Bio-Mos supplemented diets.THCs of marron fed any of the diets were reduced when they were exposed to NH3 but the THCs were higher (P<0.05) in marron fed Bio-Mos diets. Vibrio spp. in haemolymph of marron fed the control diet significantly increased when they were infected with V. mimicus and challenged with NH3 but it remained unchanged in the marron fed the Bio-Mos diets. Haemolymph clotting time was higher in marron fed the control diets when subjected to live transportation and 3 days of exposure to NH3. After 96 h infection marron fed the Bio-Mos diets had longer NRR time than those fed the control diet. All the findings demonstrated the ability of Bio-Mos to improve the survival, health status and immunity of marron under the bacterial infection and stress conditions caused by air and NH3 exposures.